A candidate gene approach for virally induced cancer with application to HIV‐related Kaposi's sarcoma. Issue 2 (27th July 2013) - Aissani, Brahim; Wiener, Howard W.; Zhang, Kui; Kaslow, Richard A.; Ogwaro, Kisani M.; Shrestha, Sadeep; Jacobson, Lisa P.
Abstract : Like other members of the γ‐herpesvirus family, human herpes virus 8, the etiologic agent of classic and HIV‐related Kaposi's sarcoma (HIV‐KS) acquired and evolved several human genes with key immune modulatory and cellular growth control functions. The encoded viral homologs substitute for their human counterparts but escape cellular regulation, leading to uncontrolled cell proliferation. We postulated that DNA variants in the human homologs of viral genes that potentially alter the expression or the binding of the encoded factors controlling the antiviral response may facilitate viral interference. To test whether cellular homologs are candidate susceptibility genes, we evaluated the association of DNA variants in 92 immune‐related genes including seven cellular homologs with the risk for HIV‐KS in a matched case and control study nested in the Multicenter AIDS Cohort Study. Low‐ and high‐risk gene‐by‐gene interactions were estimated by multifactor dimensionality reduction and used as predictors in conditional logistic models. Among the most significant gene interactions at risk (OR = 2.84–3.92; Bonferroni‐ adjusted p  = 9.9 × 10 −3 – 2.6 × 10 −4 ), three comprised human homologs of two latently expressed viral genes, cyclin D1 ( CCND1 ) and interleukin‐6 ( IL‐6 ), in conjunction with angiogenic genes ( VEGF, EDN‐1 and EDNRB ). At lower significance thresholds (adjusted p < 0.05), human homologs related to apoptosis ( CFLAR ) and chemotaxis ( CCL2 ) emerged as candidates. This "proof of concept" study identified human homologs involved in the regulation of type I interferon‐induced signaling, cell cycle and apoptosis potentially as important determinants of HIV‐KS Abstract : What's new? Human herpesvirus 8 (HHV‐8), which causes HIV‐related Kaposi's sarcoma, contains several human‐derived genes that allow unchecked cell proliferation because they operate undetected by the host immune defenses. The authors tested these homologous genes to find out whether polymorphisms there could be exploited by the viral proteins to promote the growth of the cancer. They evaluated variants of 92 genes to see whether they increased the risk of HIV‐related Kaposi's sarcoma, and they found several human homologs of viral genes related to angiogenesis, apoptosis, and immune response, among others, demonstrating proof of concept that these genes participate in the progression of the disease.